Review of the leafhopper tribe Stenometopiini (Hemiptera: Cicadellidae: Deltocephalinae) from China with description of four new species - Duan, Yani; Webb, M.d.; Zhang, Yalin (Zootaxa, 2016)
The leafhopper tribe Stenometopiini is revised from China. Two genera are included: Hodoedocus Jacobi with two species and Stirellus Osborn & Ball with thirteen species of which four are new: S. daii sp. nov., S. multipunctatus sp. nov., S. neospeciosus sp. nov., and S. translucidus sp. nov. S. yeongnamensis (Kwon & Lee) is newly recorded for China. Five new synonyms are proposed: Viridomarus brevialatus Xing et al. and Viridomarus laticellus Xing et al. as junior synonyms of S. capitatus (Distant); Aconura bipunctella Matsumura and Paivanana centristriata Dai & Li as junior synonyms of S. indrus (Distant); Aconura rubrofasciata Matsumura as junior synonym of S. rubrolineatus (Distant). Two new combinations are erected and one combination is reinstated (see checklist). Species are described and illustrated together with keys provided for their separation. Lectotypes are designated for Typhlocyba indra Distant and Arya rubrolineata Distant.